Desain Poster Promosi Jaket Wild - Alwan, Mohamad; Persada, Satria Indra Praja (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
Clothing that is used ereyday lif ca display various function and presentation. Even though one of them is the from of communication in the clothes used can be a means to convey nonverbal messages or convey information without using words. One part of delivering this information is the use of jacket for daily activities and one of them is the Wild Jacket. The purpose the promotional design is to describe the unknown Wild jacket because the conditions on the internet are not focuse and are not specifically discussed on the Wild brand. Meanwhile, what the author describe is that there is a promotion regarding the Wild jacket by having digital design work to provide interesting information on the poster. However, there are still many, especially among cimbers who do not know the creation of the Wild jacket. So from the design, the work of Wild jacket is produced by designing digital poster media to promote or advertise the work of the brand jacket, so that later the work of Wild jacket is better known to the public, especially among cimbing children.